Antiulcer Activity of Morinda Citrifolia Linn Fruit Extract - Srikanth, J.; Muralidharan, P. (Journal of Scientific Research, 2009)
The study was designed to investigate the antiulcer activity of ethyl acetate extract of the fruits of Morinda citrifolia Linn (Rubiaceae) using different models of gastric and duodenal ulceration in rats. Gastric ulcers were induced by oral administration of ethanol, aspirin and by pyloric ligation and duodenal ulcers were induced by oral administration of cysteamine HCl. The extract was administered at a dose of 200 and 400 mg/kg orally 30 min prior to ulcer induction. Ranitidine (50 mg/kg) was used as a reference standard. The antiulcer activity was accessed by determining and comparing the ulcer index in the test group with that of the standard drug treated group. Gastric volume, total acid and free acid were estimated in the pylorus-ligated rats. M.citrifolia (400mg/kg) showed maximum inhibition of gastric acid, free acid and total acid to 53.54%, 52.55% and 30.30%, respectively. The ulcer index in the M.citrifolia treated animals was found to be significantly less in all the models compared to standard drug treated cases. The antiulcer activity of M.citrifolia was, however, less than that of ranitidine. The results suggest that M.citrifolia possesses significant antiulcer property which could be due to cytoprotective action of the drug or strengthening of gastric and duodenal mucosa with the enhancement of mucosal defence. Keywords: Morinda citrifolia; Antiulcer. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.1625